GENDER ANALISIS PERAN PEREMPUAN DALAM MENCARI NAFKAH DI ERA PANDEMI COVID-19 - Aisyah, Aisyah; Susanti, Neila; Jailani, Muhammad (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
The role of a housewife who makes a living to meet economic needs and as we know since the existence of this pandemi in helping to make a living and meet household needs, which should be as we know that a housewife who should only work at home but they should take part in helping to make a living to meet economic needs which we know is very devastated economic life in Indonesia  which is not bad according to the Covid-19 pandemi because of the large number of workers' expenses due to the pandemi and that's where housewives take over to make a living which as we know that a woman or housewife is supposed to take care of the household but they have to participate in making a living. To find out how the multiple roles played by housewives to make a living in the era of the Covid -19 pandemic which aims to trigger conflicts that lead to gender equality. In this study, the authors used a qualitative method with a descriptive approach and used interviews where the data collected was in the form of words, pictures, and not numbers. In that sense (Moleong 2017) in this study describes and understands the existence of events in society that are considered to belong to social deviations with a qualitative descriptive approach.